(untitled) (Fiep Bulletin - online, 2013)
This is a descriptive research, of the quantitative type, being the sample was composed for 49 students, being 28 of feminine sort and 21 of the masculine, of 6 to the 15 years of age, regularly registered of 1° to 5° year of basic education. We measured it flexibility with the protocol of indirect and linear measure of flexibility of Wells and Dillon, the corporal weight and the corporal stature (MELO, 2005). A very low level of flexibility in all was evidenced the evaluated groups (1°, 2°, 3°, 4° and 5° year). The study necessity pointed it to extend the offer of lessons of Physical Education in the initial series.